Jack London, his life, work and legacy - Cabrera Espinoza, María Eugenia; Soto Portuguez, Carmen Elena
Jack London is not just an author of dog stories. He is according to some literary critics, one of the greatest writers in the world. His stories are read worldwide more than any other American author, alive or dead, and he is considered by many as the American finest author. This work presents Jack London as a man who is valiant, wise, adventurous, a good worker, and a dreamer who tries to achieve his goals. He shows that poverty is not an obstacle to get them. His youth experiences inspire him to create his literary works. His work exemplifies traditional American values and captures the spirit of adventure and human interest. His contribution to literature is great. We can find in his collection of works a large list of genders like novels, short stories, non-fiction, and autobiographical memoirs. These genders contain a variety of literary styles, adventure, drama, suspense, humor, and even romance. Jack London gets the materials of his books from his own adventures; his philosophy was a product of his own experiences; his love of life was born from trips around the world and voyages across the sea. Through this work we can discover that the key of London´s greatness is universality that is his work is both timely and timeless.